Trends in performance indicators of English Premiership Rugby teams - Kvasnytsya, O.; Tyshchenko, V.; Latyshev, M.; Kvasnytsia, I.; Timasheva, O.; Rybak, L.; Flerchuk, V.; Omelchuk, M. (Trends in Sport Sciences, 2025)
Introduction: Sport continuously evolves in response to modern challenges, with data analysis playing a pivotal role in understanding trends and predicting future developments. In team sports, including rugby, performance indicators are critical for optimizing training processes and enhancing competitive effectiveness.